Peningkatan Pengetahuan Tentang Napza Pada Kader Remaja Parikesit - Ferianto Ferianto; Ratna Lestari; Khristina Dias Utami; Masta Hutasoit (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2023)
This community service aims to assist Puksemas in creating a drug-free society through the revitalization of the Parikesit Posyandu program. The method of activity carried out is with assistance and technical guidance through health education, lectures and discussions, as well as monitoring program evaluation. The target for this community service is all youth in Tirtomartani Village, especially the management of Parikesit Posyandu cadres. The activities were carried out starting from preparation to evaluation, which were carried out on November 10-30 2021. Assistance activities began with coordinating program implementation, counseling activities and assisting in the evaluation of the programs being carried out. The final assistance aims to increase knowledge about drugs for adolescents in Tirtomartani Village. The community service which was carried out in the Tirtomartani Village was attended by 21 Parikesit youth cadres. Knowledge of youth cadres before and after drug education increased knowledge with a mean pretest score of 62.38 and a mean posttest score of 95.24. So there is an increase of 32.86. Based on the Paired T-Test statistical test, there is a significant difference between knowledge before and after being given counseling about drugs with a p value of 0.000. Assistance is needed from the Kalasan health center so that Parikesit youth cadres can apply the knowledge they have gained so that they can assist the Puskesmas in carrying out drug prevention and control in adolescents.